Diffusion of Ethanol in Supercritical Carbon Dioxide—Investigation of scCO2-Cosolvent Mixtures Used in Pharmaceutical Applications - Santos, Cecília I. A. V. (2022)
Diffusion coefficients, D, for ethanol in supercritical carbon dioxide (scCO2) were measured in the temperature range 306.15–331.15 K and along the 10.5MPa isobar, using the Taylor dispersion technique. The obtained diffusivities ranged from 1.49 108 to 2.98 108 m2 s1, an order of magnitude higher than in usual liquids. The dependence of D on temperature and solvent density was examined. Various correlation models based in the hydrodynamic theory were assessed to estimate the diffusion coefficients, with reasonable results obtained for theWilke–Chang and Lai–Tan models.